Treelike two-level PdₓAgᵧ nanocrystals tailored for bifunctional fuel cell electrocatalysis - Jiang, Xian (2021)
Pd-based alloy catalysts have been extensively investigated as the anodic and cathodic catalysts of direct formic acid fuel cells (DFAFCs) by virtue of their unique synergistic effect, good stability and relatively low cost compared with Pt-based alloy catalysts. Controlling the structure and morphology of nanocatalysts is of great significance to tune and boost their electrocatalytic performance. Herein, we propose a simple, rapid and green approach to fabricate tree-like PdAg nanocrystals with tunable chemical composition (PdₓAgᵧ NTs) via mixing the metal precursors and 1-naphthol, and then aging for a mere 30 min at 60 °C. The obtained PdₓAgᵧ NTs feature a two-level structure of tiny Pd₁Ag₃ alloy nanodendrites and Pd₁Ag₂ alloy nanobranches with abundant active sites and enhanced structural stability. The formation mechanism of PdₓAgᵧ NTs has been investigated well via a series of control experiments, which is just like the germination and growth of a tree. To the best of our knowledge, treelike two-level PdₓAgᵧ nanostructures have never been reported before. Electrochemical measurements demonstrate that the Pd₃Ag₁ NTs outperform commercial Pd black and other compositional Pd₁Ag₁ and Pd₁Ag₃ NTs in the aspects of bifunctional activity and stability towards the anodic formic acid oxidation and cathodic oxygen reduction of the DFAFCs.